l‐Carnitine relieves cachexia‐related skeletal muscle fibrosis by inducing deltex E3 ubiquitin ligase 3L to negatively regulate the Runx2/COL1A1 axis - Zongliang Lu; Li Wang; Zhenyu Huo; Na Li; Ning Tong; Feifei Chong; Jie Liu; Yaowen Zhang; Hongxia Xu (Wiley, 2024)
Abstract Background Cancer cachexia‐induced skeletal muscle fibrosis (SMF) impairs muscle regeneration, alters the muscle structure and function, reduces the efficacy of anticancer drugs, diminishes the patient's quality of life and shortens overall survival. RUNX family transcription factor 2 (Runx2), a transcription factor, and collagen type I alpha 1 chain (COL1A1), the principal constituent of SMF, have been linked previously, with Runx2 shown to directly modulate COL1A1 mRNA levels. l‐Carnitine, a marker of cancer cachexia, can alleviate fibrosis in liver and kidney models; however, its role in cancer cachexia‐associated fibrosis and the involvement of Runx2 in the process remain unexplored. Methods Female C57 mice (48 weeks old) were inoculated subcutaneously with MC38 cells to establish a cancer cachexia model. A 5 mg/kg dose of l‐carnitine or an equivalent volume of water was administered for 14 days via oral gavage, followed by assessments of muscle function (grip strength) and fibrosis. To elucidate the interplay between the deltex E3 ubiquitin ligase 3L(DTX3L)/Runx2/COL1A1 axis and fibrosis in transforming growth factor beta 1‐stimulated NIH/3T3 cells, a suite of molecular techniques, including quantitative real‐time PCR, western blot analysis, co‐immunoprecipitation, molecular docking, immunofluorescence and Duolink assays, were used. The relevance of the DTX3L/Runx2/COL1A1 axis in the gastrocnemius was also explored in the in vivo model. Results l‐Carnitine supplementation reduced cancer cachexia‐induced declines in grip strength (>88.2%, P < 0.05) and the collagen fibre area within the gastrocnemius (>57.9%, P < 0.05). At the 5 mg/kg dose, l‐carnitine also suppressed COL1A1 and alpha‐smooth muscle actin (α‐SMA) protein expression, which are markers of SMF and myofibroblasts. Analyses of the TRRUST database indicated that Runx2 regulates both COL1A1 and COL1A2. In vitro, l‐carnitine diminished Runx2 protein levels and promoted its ubiquitination. Overexpression of Runx2 abolished the effects of l‐carnitine on COL1A1 and α‐SMA. Co‐immunoprecipitation, molecular docking, immunofluorescence and Duolink assays confirmed an interaction between DTX3L and Runx2, with l‐carnitine enhancing this interaction to promote Runx2 ubiquitination. l‐Carnitine supplementation restored DTX3L levels to those observed under non‐cachectic conditions, both in vitro and in vivo. Knockdown of DTX3L abolished the effects of l‐carnitine on Runx2, COL1A1 and α‐SMA in vitro. The expression of DTX3L was negatively correlated with the levels of Runx2 and COL1A1 in untreated NIH/3T3 cells. Conclusions This study revealed a previously unrecognized link between Runx2 and DTX3L in SMF and demonstrated that l‐carnitine exerted a significant therapeutic impact on cancer cachexia‐associated SMF, potentially through the upregulation of DTX3L.